Entangled security: Science, co-production, and intra-active insecurity. (June 2019) - Elbe, Stefan; Buckland-Merrett, Gemma
Abstract: This article advances a new account of security as an intensely relational and ontologically entangled phenomenon that does not exist prior to, nor independently of, its intra-action with other phenomena and agencies. Security's 'entanglement' is demonstrated through an analysis of the protracted security concerns engendered by 'dangerous' scientific experiments performed with lethal H5N1 flu viruses. Utilising methodological approaches recently developed in the field of Science and Technology Studies (STS), the article explicates the intensely 'co-productive' dynamics at play between security and science in those experiments, and which ultimately reveal security to be a deeply relational phenomenon continuously emerging out of its engagement with other agencies. Recovering this deeper ontological entanglement, the article argues, necessitates a different approach to the study of security that does not commence by fixing the meaning and boundaries of security in advance. Rather, such an approach needs to analyse the diverse sites, dynamics, and processes through which security and insecurity come to intra-actively materialise in international relations. It also demands a fundamental reconsideration of many of the discipline's most prominent security theories. They are not merely conceptual tools for studying security, but crucial participants in its intra-active materialisation.